Moral Value in “Wonder” Movie Directed by Stephen Chbosky (2017) - Arfani, Sri; Puspita, Vira Ayu (STIBA IEC JAKARTA, 2025)
Moral value is a very important thing in our life and it becomes a basic need of every human in the world. This research conducts a literary analysis focused on the moral values embodied in the film